The Mathematical Foundations of Economic Theory - Allen, R. G. D. (Quarterly Journal of Economics, 1949)
I. General comments: the use of mathematics by Hicks and by Samuelson, 111. — II. Samuelson's treatment of cost and production, 114. — III. Hicks and Samuelson on consumers' demand, 118. — IV. Samuelson's dynamics: difference equations, 121.